Pulmonary Congestion Assessed by Lung Ultrasound and Cardiovascular Outcomes in Patients With ST-Elevation Myocardial Infarction - Araiza-Garaygordobil, Diego; Baeza-Herrera, Luis A.; Gopar-Nieto, Rodrigo; Solis-Jimenez, Fabio; Cabello-López, Alejandro; Martinez-Amezcua, Pablo; Sarabia-Chao, Vianney; González-Pacheco, Héctor; Sierra-Lara Martinez, Daniel; Briseño-De la Cruz, José Luis; Arias-Mendoza, Alexandra (Frontiers in Physiology, 2022)
Background: Lung ultrasound (LUS) shows a higher sensitivity when compared with physical examination for the detection of pulmonary congestion. The objective of our study was to evaluate the association of pulmonary congestion assessed by LUS after reperfusion therapy with cardiovascular outcomes in patients with ST-segment Elevation acute Myocardial Infarction (STEMI) who received reperfusion therapy. Methods: A prospective observational study including patients with STEMI from the PHASE-Mx study. LUS was performed in four thoracic sites (two sites in each hemithorax). We categorized participants according to the presence of pulmonary congestion. The primary endpoint of the study was the composite of death for any cause, new episode or worsening of heart failure, recurrent myocardial infarction and cardiogenic shock at 30 days of follow-up. Results: A total of 226 patients were included, of whom 49 (21.6%) patients were classified within the “LUS-congestion” group and 177 (78.3%) within the “non-LUS-congestion” group. Compared with patients in the “non-LUS-congestion” group, patients in the “LUS-congestion” group were older and had higher levels of blood urea nitrogen and NT-proBNP. Pulmonary congestion assessed by LUS was significantly associated with a higher risk of the primary composite endpoint (HR: 3.8, 95% CI 1.91-7.53, p=0.001). Differences in the primary endpoint were mainly driven by an increased risk of heart failure (HR 3.91; 95%CI 1.62-9.41, p=0.002) and cardiogenic shock (HR 3.37; 95%CI 1.30–8.74, p=0.012). Conclusions: The presence of pulmonary congestion assessed by LUS is associated with increased adverse cardiovascular events, particularly heart failure and cardiogenic shock. The application of LUS should be integrated as part of the initial risk stratification in patients with STEMI as it conveys important prognostic information.